2016
DOI: 10.7150/thno.14158
|View full text |Cite
|
Sign up to set email alerts
|

Dihydropyrimidine Dehydrogenase Is a Prognostic Marker for Mesenchymal Stem Cell-Mediated Cytosine Deaminase Gene and 5-Fluorocytosine Prodrug Therapy for the Treatment of Recurrent Gliomas

Abstract: We investigated a therapeutic strategy for recurrent malignant gliomas using mesenchymal stem cells (MSC), expressing cytosine deaminase (CD), and prodrug 5-Fluorocytosine (5-FC) as a more specific and less toxic option. MSCs are emerging as a novel cell therapeutic agent with a cancer-targeting property, and CD is considered a promising enzyme in cancer gene therapy which can convert non-toxic 5-FC to toxic 5-Fluorouracil (5-FU). Therefore, use of prodrug 5-FC can minimize normal cell toxicity. Analyses of mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 32 publications
(37 reference statements)
0
21
0
Order By: Relevance
“…The orotate phosphoribosyl transferase (OPRT) expression level of HT-29/EGFP/FUR cells was decreased, which would correspond with decreased activation of 5-FU, thus initial conversion of 5-FU to 5-FUMP. It was shown on a model of glioblastoma cell lines [26] that dihydropyrimidine dehydrogenase (DPD) can be used as a biomarker for selecting glioma patients who may benefit from the CD-MSC/5-FC therapy. Considering the ability of DPD to deplete 5-FU, it is reasonable to expect that DPD-deficient tumors would be more sensitive to this treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The orotate phosphoribosyl transferase (OPRT) expression level of HT-29/EGFP/FUR cells was decreased, which would correspond with decreased activation of 5-FU, thus initial conversion of 5-FU to 5-FUMP. It was shown on a model of glioblastoma cell lines [26] that dihydropyrimidine dehydrogenase (DPD) can be used as a biomarker for selecting glioma patients who may benefit from the CD-MSC/5-FC therapy. Considering the ability of DPD to deplete 5-FU, it is reasonable to expect that DPD-deficient tumors would be more sensitive to this treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the 5‐FC/CD system also possesses a powerful bystander effect that diffuses 5‐FU into neighboring non‐transfected cells. In some recent studies, non‐viral vector‐encapsulated plasmid DNA encoding CD has shown effective antitumor efficacy with the addition of 5‐FC both in vitro and in vivo , greatly encouraging further investigation via clinical trials of the treatment of brain tumors using the CD/5‐FC suicide gene therapy system.…”
Section: Therapeutic Genes For Cns Diseasesmentioning
confidence: 99%
“…The growth rate has been previously shown to influence sensitivity of glioma cells to anti-cancer drug (Chung et al 2016). Thus, the cells' growth rate in Clk1 knockdown and control cells was measured by cell count (Fig.…”
Section: Clk1 Level Correlates With the Chemosensitivity Of Glioma Cellsmentioning
confidence: 99%